Academic results and sociometric status in Secondary Education - Ramos Corpas, Manuel Jesús; Castillo García, Manuel; Revuelta Marchena, Manuel (Avances en Supervisión Educativa, 2016)
In this research in an obligatory secondary education center to a sample of 407 students, a sociometric technique has been used to establish the sociometric types of rejected, popular and average from individual rates of antipathy, popularity and sociometric status. First objective results have been studied depending on course and sex. As a second objective the correlational model has been used to calculate interactions between academic performance (through the variable number of failures) and individual rates mentioned above constituted in variables. The main results show, concerning the first objective, that there is more number of students rejected than popular. Also that the highest percentage of students rejected typology occurs in the second year of obligatory secondary education and that there is a higher percentage of rejected and popular considering the male sex. In relation to the second objective significant correlations were obtained in all the variables analyzed. Finally the results are discussed.